Reduced immune responsiveness contributes to winter energy conservation in an Arctic bird - Nord, Andreas; Arne, Hegemann; Folkow, Lars (Journal of Experimental Biology, 2020)
Animals in seasonal environments must prudently manage energy expenditure to survive the winter. This may be achieved through reductions in the allocation of energy for various purposes (e.g. thermoregulation, locomotion, etc.). We studied whether such trade-offs also include suppression of the innate immune response, by subjecting captive male Svalbard ptarmigan ( Lagopus muta hyperborea ) to bacterial lipopolysaccharide (LPS) during exposure to either mild temperature (0°C) or cold snaps (acute exposure to −20°C), in constant winter darkness when birds were in energy-conserving mode, and in constant daylight in spring. The innate immune response was mostly unaffected by temperature. However, energy expenditure was below baseline when birds were immune challenged in winter, but significantly above baseline in spring. This suggests that the energetic component of the innate immune response was reduced in winter, possibly contributing to energy conservation. Immunological parameters decreased (agglutination, lysis, bacteriostatic capacity) or did not change (haptoglobin/PIT54) after the challenge, and behavioural modifications (anorexia, mass loss) were lengthy (9 days). While we did not study the mechanisms explaining these weak, or slow, responses, it is tempting to speculate they may reflect the consequences of having evolved in an environment where pathogen transmission rate is presumably low for most of the year. This is an important consideration if climate change and increased exploitation of the Arctic would alter pathogen communities at a pace outwith counter-adaption in wildlife.